Expression of Axiological Assessment of Birliclarining in Artistic Text (Texas Journal of Multidisciplinary Studies, 2023)
The presence of axiological modality in works of art is reflected in the psyche of the author of the work, and it is transferred to the artistic text. The axiological modality in the literary text with the participation of detached explanatory clauses is the manifestation of the author's purpose (overt or hidden) in the text of the initiators of speech activity. In this process, the assessment of reality is combined with the act of description. This article discusses such issues.